N-Induced Species Loss Dampened by Clipping Mainly Through Suppressing Dominant Species in an Alpine Meadow - Wu, Wenyuan; Wang, Xiangtai; Ren, Zhengwei; Zhou, Xianhui; Du, Guozhen (Frontiers in Plant Science, 2022)
Nitrogen addition and clipping can exert substantial impact on species diversity but their interactions and the underlying mechanisms still remain unclear. Resource competition theory holds that sufficiently strong competitive ability of dominant species can lead to the losses of subordinate species through competitive exclusion, while niche differentiation theory suggests that the persistence of subordinate species in competitive systems can be promoted by guaranteeing positive growth rates of rare species. Taking advantage of a field experiment with nitrogen addition (10 g N m–2 year–1) and different clipping intensities (2, 15, and 30 cm) treatments in a Tibetan alpine meadow across 2015–2020, we assessed the relative importance of competitively dominant species and niche differentiation in driving species diversity changes via using community weighted mean (CWM) and variation coefficient of nearest neighbor distance (CV_NND) of functional traits including height, specific leaf area (SLA) and leaf dry matter content (LDMC). We show that nitrogen enrichment drove a strong plant diversity loss (P < 0.001). Clipping at different intensities had little effect on species diversity, but it can reduce the N-induced diversity loss. Nitrogen addition and clipping caused changes in community diversity were mainly indirectly attributed to their effects on community functional composition, and the competitive ability of dominant species. Nitrogen increased the CWM of functional traits to improve the competitive ability of dominant species. In contrast, clipping influenced species diversity positively by decreasing CWMheight (P < 0.001), and also negatively by increasing CWMSLA (P < 0.001) and decreasing CV_NNDSLA (P < 0.05). Interacting with N addition, clipping resulted in a neutral effect on species diversity, because clipping could offset the negative effects of nitrogen addition through an opposite effect on CWMheight. This study provides new insights into the mechanisms of diversity maintenance with respect to nitrogen addition and clipping. Thus, clipping is recommended as a useful management strategy to alleviate the species loss caused by nutrients enrichment and maintain the diversity of grassland ecosystems.